Proton pump coupled to cytochrome c oxidase in the cyanobacterium Anacystis nidulans. - Peschek, G A (1983)
Intact spheroplasts of the cyanobacterium Anacystis nidulans were found to oxidize various exogenous c-type cytochromes with concomitant proton extrusion. In the coupled state, H+/e stoichiometries close to 1 were measured, regardless of absolute reaction rates. It is concluded that the proton translocation observed is an intrinsic property of the cytoplasmic membrane-bound cytochrome c oxidase of A. nidulans.